Citizen preparedness campaign : information campaigns increasing citizen preparedness to support creating a 'Culture of Preparedness' - Bloom, Paula S. (Monterey, California. Naval Postgraduate School, 2007)
CHDS State/Local Citizen preparedness has been a requirement since the events of September 11, 2001, and was reinforced as a necessity after Hurricanes Katrina and Rita in August 2005. Although National Strategy documents outline the requirement for citizen participation in national preparedness the requirement is through volunteerism using the Citizen Corps. There are currently readiness programs being conducted through the Citizen Corps, Department of Homeland Security and the Federal Emergency Management Agency but they are not coordinated across the federal state and local or proactive in nature. Proactive Information Campaigns using core and supporting elements can be one methodology to increase citizen preparedness to support the creation of a 'Culture of Preparedness', which includes citizen participation along with the all levels of government and the private sector. Homeland Security stakeholders can use the Information Campaign Model developed to formulate proactive information campaigns to increase citizen preparedness. Lieutenant Commander (LCDR), US Northern Command (Northcom) author. http://archive.org/details/citizenpreparedn109453650